ORTUMAN: Inovasi Media Pembelajaran Berbasis Android dengan Pendekatan Visual Auditory Kinesthetic (VAK) - Heri Kuswanto; Rasyid Hardi Wirasasmita; Arman Hadi (Infotek: Jurnal Informatika dan Teknologi, 2023)
This study aims to produce android-based learning media in the science subject material Organs of Movement of Animals and Humans, Theme 1, by applying the Visual Auditory Kinesthetic Model (VAK) learning style. This type of research uses the Development (R&D) model, and the development procedure used is Agile development, which consists of five stages: requirements, design, development, testing, deployment, and Review. The subjects in this study were 19 students of class V, MI NW No. 3, Pancor, to find out the user's response. This research is limited to the product development and feasibility testing of Android-based learning media products. Data collection techniques include observation, interviews, and questionnaires, as well as data analysis using descriptive and qualitative methods. The results of the authors show that the developed Android-based learning media obtained the results of the material expert feasibility test with very feasible results, and the results of the media expert feasibility test were very feasible, and the results of user response trials from the aspects of content suitability, learning quality, and media quality showed that Android-based learning media in the science subject material Organs of Movement of Animals and Humans Theme 1 by applying the Visual Auditory Kinesthetic Model (VAK) learning style is feasible to use and has a high response as an innovation in the learning process